Kehamilan Ibu di Usia Muda dengan Perkembangan Emosi Anak Usia 3-5 Tahun di Wilayah Kerja Puskesmas Sewon II Kabupaten Bantul - Hastin Laili Mukharromah; Yuni Kusmiyati; Margono Margono (Jurnal Kesehatan Ibu dan Anak, 2017)
The prevalence of emotional and behavioral disorders in preschool children was very high at 34.10%. One of the factors of child'semotional development problem was mother's age when pregnant. . The aim of this study was to determine the relationship ofmaternal pregnancy at a young age with emotional development of children aged 3-5 years. This study used historical cohort design.The subjects were all pregnant mothers in the working area of Puskesmas Sewon II Bantul Yogyakarta in 2012-2014. The sample ofthis study amounted to 74 respondents. The independent variable was an emotional development assessed using the Strength andDifficulties Questionnaire (SDQ) questionnaire. The dependent variable was the age of the mother. External variables that were alsostudied were parenting, number of children, gender of children, education, and parent's income. Data analysis used chi square andlogistic regression. Research shows there was a relationship between pregnancy at a young age with emotional development ofchildren aged 3-5 years. Children aged 3-5 years who were born from mothers who are pregnant at a young age and have 80%chance of experiencing emotional development disorders than adult mothers. For that teenager, family, and health workers to beable to prevent pregnancy young age with health promotion to avoid the occurrence of emotional disturbance of children aged 3-5years.